Description of Mathematical Connection Ability From Student Learning Styles In Online LearningUsing Discovery-Based Worksheets - Ujang Suprianto; Aan Hendrayana; Syamsuri Syamsuri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This study aims to determine the description of the mathematical connection ability of class XI MIPA students based on the learning styles of students of convergers, divergers, accommodators, and assimilators in online learning using discovery-based worksheets. This type of research is a qualitative descriptive study. The subjects of the study were the students of class XI MIPA SMAN 17 Pandeglang. Data collection is done through learning style questionnaires, tests of mathematical connection abilities, and interviews. All students of class XI MIPA were identified by the type of learning style using the Kolb learning style questionnaire. Data about mathematical connection ability is analyzed with interview data. 8 students consisting of 2 students representing learning styles were selected to interview their mathematical connection abilities. Based on the analysis of the data obtained a description of the results of research that in general students of the type of converger, diverger, accomodator, and assimilator have good mathematical connection abilities. the assimilator type is rather weak on the indicator using the mathematical connection ability indicator. As for the type of accomodation learning style, it is rather weak in finding and understanding concepts in mathematical connection abilities. Students of the Converger learning style style and assimilator understand the material by reading and observing in the ongoing learning while students of the Diverger learning style type and the accomodator understand the concepts in general by following the learning process in progress and actively trying to try in working on the discovery-based worksheets.